Behavior–biological mismatch in metabolic health: Evidence from South Korean adults before, during, and after COVID-19 (KNHANES 2019–2022) - Yoo Mi Jeong; Minjeong Kim; Jae Yeon Jeong (PLoS ONE, 2026)
Objective Regular physical activity (PA) is recommended for cardiometabolic prevention, yet emerging evidence suggests that meeting PA guidelines alone does not guarantee metabolic health. Pandemic-related disruptions may have intensified behavior–biology discrepancies. This study examined the prevalence and sociodemographic determinants of the physically active but metabolically unhealthy (PA–NH) group before, during, and after the COVID-19 pandemic in Korea. Methods We analyzed 17,719 adults aged ≥19 years using the 2019–2022 Korea National Health and Nutrition Examination Survey. Participants were classified into four groups: PA–H, NPA–H, NPA–NH, and PA–NH. Temporal patterns across the pre- (2019), during- (2020–2021), and post-pandemic period (2022) were assessed using χ² tests and ANOVA. Multinomial logistic regression identified determinants of PA–NH membership. Results From 2019 to 2022, PA–H declined during the pandemic and rebounded thereafter, whereas PA–NH increased from 31.2% to 34.0%. Older adults had markedly higher odds of PA–NH (OR 7.30 for ≥70 y vs 19–29 y). Women were less likely to belong to PA–NH. Higher education reduced the odds of mismatch relative to PA–H but increased them compared with NPA–NH. Metabolic risk factors such as hypertension and hypercholesterolemia rose despite recovery in PA. Conclusions The persistence and rise of PA–NH after the pandemic show an association suggesting that adherence to PA guidelines alone is insufficient for cardiometabolic protection. Post-pandemic public health strategies should integrate aerobic and resistance exercise with dietary modification, stress management, and routine screening, prioritizing older adults and other high-risk groups.